The Art of Drug Design and Process Chemistry - Mohd. Wasiullah; Piyush Yadav; Sushil Yadav; Roshan Yadav (International Journal of Bioinformatics and Computational Biology, 2025)
The creation of safe and efficient medications depends heavily on the art of drug design and process chemistry. This multidisciplinary discipline designs and optimizes drug candidates for therapeutic uses by fusing the concepts of biology, chemistry, and engineering. Researchers can develop compounds with pharmacological activity by using logical drug design techniques if they have a thorough understanding of the molecular targets implicated in disease pathways. By making it easier to predict molecular interactions and properties, computational techniques significantly improve the drug discovery process. These theoretical concepts are then translated into workable synthesis pathways, purification techniques, and scale-up procedures that are necessary to produce pharmaceuticals by process chemistry. This article delves into the complexities of process chemistry and drug design, examining the core ideas and real-world uses that spur innovation in Pharmaceutical Development.
Keywords: De novo design; Rational drug design; drug design; pharmacophore